An effective approach to enhance the balancing control in bycycorobot using the soft computing techniques - Sharma, Aswant Kumar; Sambariya, Dhanesh Kumar (Institute of Advanced Engineering and Science, 2022)
The balancing and control of bycycorobot is a challenging task. The pre-specified controller available in the literature for balancing has been reduced with novel optimization to improve the effectiveness of balancing, uncertainty, and the complexity of the complete system. The novel Harris hawk optimization (HHO) which is based on the hunting behavior of the hawk has been utilized to improve the balancing of the bycycorobot. The paper proposes the decreased order controller of a pre-specified controller for a bycycorobot. The obtained controller response with bycycorobot in the complete closed loop is analyzed, and the best performance is compared with the reduced order controller available in the literature. The comparison is based on the response indices and response characteristics.